HVAC : handbook of heating, ventilation and air conditioning for design and implementation - Vedavarz, Ali (Industrial Press, 2007)
A comprehensive handbook and essential reference, providing instant access to all the data, calculations, and equations needed for modern HVAC design.
Keywords: Heating -- Handbooks, manuals, etc.; Ventilation -- Handbooks, manuals, etc.; Air conditioning -- Handbooks, manuals, etc.; Buildings -- Environmental engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books